2015
DOI: 10.1073/pnas.1505420112
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescence molecular imaging of amyloid beta species and monitoring therapy in animal models of Alzheimer’s disease

Abstract: Near-infrared fluorescence (NIRF) molecular imaging has been widely applied to monitoring therapy of cancer and other diseases in preclinical studies; however, this technology has not been applied successfully to monitoring therapy for Alzheimer's disease (AD). Although several NIRF probes for detecting amyloid beta (Aβ) species of AD have been reported, none of these probes has been used to monitor changes of Aβs during therapy. In this article, we demonstrated that CRANAD-3, a curcumin analog, is capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
180
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(184 citation statements)
references
References 85 publications
2
180
0
Order By: Relevance
“…In recent years, the molecular imaging with fluorescent probes has been widely applied to monitoring therapy of cancer and other diseases in preclinical studies (12,48,49). In this study, we firstly established an enzyme replacement imaging system to visualize the intracellular β-Hex activity of modified HexBs incorporated into living cultured SD fibroblasts with a newly developed fluorescent substrate, HMDER-βGlcNAc specific for the β-Hex, based on the design of previous report (48,50).…”
Section: Animals Sd Model Mice (Hexb -/-mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the molecular imaging with fluorescent probes has been widely applied to monitoring therapy of cancer and other diseases in preclinical studies (12,48,49). In this study, we firstly established an enzyme replacement imaging system to visualize the intracellular β-Hex activity of modified HexBs incorporated into living cultured SD fibroblasts with a newly developed fluorescent substrate, HMDER-βGlcNAc specific for the β-Hex, based on the design of previous report (48,50).…”
Section: Animals Sd Model Mice (Hexb -/-mentioning
confidence: 99%
“…This fluorescent probe will also be useful for imaging or chase of other lysosomal enzymes and related proteins in acidic cellular compartments (late endosomes/lysosomes). Near-infrared fluorescence molecular imaging of amyloid β species and monitoring therapy in animal models of AD was reported (49). Such monitoring methods with fluorescent probes capable of assisting drug development is highly desirable for monitoring therapy of neurological disorders for not only preclinical studies using animal disease models, but also clinical trials and applications to disease patients.…”
Section: Animals Sd Model Mice (Hexb -/-mentioning
confidence: 99%
“…F luorescence-based optical imaging is a broadly applied imaging technique that provides a nondestructive means for detecting disease, monitoring disease progression, and evaluating treatment outcome (1)(2)(3)(4). Compared with tomographic imaging techniques, such as magnetic resonance imaging and computed tomography, fluorescence imaging yields quicker results at a lower cost (5).…”
mentioning
confidence: 99%
“…However, utilizing this method for cascade signal amplification has not been explored. In our previous studies, we demonstrated that CRANAD-58 was a "smart" NIRF probe for Aβ s, and displayed about a 100-fold intensity increase after binding to Aβ s [28][29][30][31] . To achieve cascade signal amplification, we integrated our previous Aβ "smart" probe strategy into the design of an H 2 O 2 responsive probe.…”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively calculate the relative H 2 O 2 changes during ageing and longitudinal therapy monitoring, we will use the ratio between CRANAD-88 and CRANAD-3 (R H 2 O 2 = R (CRANAD-88) /R (CRANAD-3) ). For CRANAD-3, our previous data showed that it could reflect the changes in Aβ s during ageing and treatment 31 . Using the ratio of the two probes, we will be able to reliably calculate relative H 2 O 2 changes in the longitudinal studies.…”
Section: Monitoring H 2 O 2 Scavenging In Vivomentioning
confidence: 99%